Exploring links between social protection, gender, and climate resilience in the Sahel region - Adeyeye, Olajumoke; Fischer, Gundula (CGIAR Initiative on Gender Equality, 2023)
Research on gender issues in climate adaptation and resilience on the one hand and investigations on gendered outcomes of social protection programs on the other hand have remained largely separate. This narrative review explores the gap between both bodies of gender research with a specific focus on the Sahel region. The Gender- Responsive Age-Sensitive Social Protection (GRASSP) framework is used to assess the (still limited) evidence on connections between gender, social protection, and climate change in six gender equality outcome areas— economic security and empowerment, women’s voice and agency, protection, health, education, and psychosocial well-being. Emerging linkages between both research strands include interactions between climate adaptation strategies and features of social protection programs. Also, the importance of addressing inequitable gender norms in social protection design as well as for climate resilience became evident in several GRASSP areas. Overall, engagement between both research communities needs to be strengthened, for instance through the research questions provided.